The cAMP Response Element- Binding Protein/Brain-Derived Neurotrophic Factor Pathway in Anterior Cingulate Cortex Regulates Neuropathic Pain and Anxiodepression Like Behaviors in Rats - Wen, Jing; Xu, Yaowei; Yu, Zhixiang; Zhou, Yifan; Wang, Wenting; Yang, Jingjie; Wang, Yiming; Bai, Qian; Li, Zhisong (Frontiers in Molecular Neuroscience, 2022)
Neuropathic pain is often accompanied by anxiety and depression-like manifestations. Many studies have shown that alterations in synaptic plasticity in the anterior cingulate cortex (ACC) play a critical role, but the specific underlying mechanisms remain unclear. Previously, we showed that cAMP response element-binding protein (CREB) in the dorsal root ganglion (DRG) acts as a transcription factor contributing to neuropathic pain development. At the same time, brain-derived neurotrophic factor (BDNF), as important targets of CREB, is intricate in neuronal growth, differentiation, as well as the establishment of synaptic plasticity. Here, we found that peripheral nerve injury activated the spinal cord and ACC, and silencing the ACC resulted in significant relief of pain sensitivity, anxiety, and depression in SNI rats. In parallel, the CREB/BDNF pathway was activated in the spinal cord and ACC. Central specific knockdown and peripheral non-specific inhibition of CREB reversed pain sensitivity and anxiodepression induced by peripheral nerve injury. Consequently, we identified cingulate CREB/BDNF as an assuring therapeutic method for treating neuropathic pain as well as related anxiodepression.